Decomposição do peróxido de hidrogênio sobre catalisadores de paládio - Voll, Fernando Augusto Pedersen (2008)
Hydrogen peroxide decomposition is an undesirable reaction in the direct H2O2 synthesis process from H2 and O2. It s a desirable reaction for the generation of hydroxyl radicals (-OH) in the advanced oxidation processes. Thus, it is important to understand how the reaction medium conditions affect the H2O2 decomposition. In this work, the influence of the initial concentration of H2O2, the reaction temperature, the catalyst treatment with H2 and the catalyst deactivation (or activation) with H2O2 were studied. The catalysts studied in this work were a 5% Pd/C, a 0,5% Pd/C, a 1% Pd/g-Al2O3, and a 1% Pd/ZrO2. With the exception of the 1% Pd/ZrO2 catalyst, the apparent reaction rate constant (k) was affected by the initial concentration of H2O2 in the reaction medium, and in all cases where the reaction rate constant (k) was affected, its value decreased with the increase of the initial concentration of H2O2. The activation energy value was calculated for all the catalysts and varied between 25 and 55 kJ/mol. For all the catalysts tested, treatment with hydrogen resulted in a significant increase in the apparent reaction rate constant (k), and in a decrease in the activation energy for the reaction. All the reactions were well represented by a first order rate law. The effect of the treatment with H2O2 (realization of successive reactions of H2O2 decomposition, without catalyst exchange) was studied for the 5% Pd/C and 0,5% Pd/C catalysts (exposed to H2 or not). A small deactivation was observed in the 5% Pd/C catalyst (without prior exposure to H2) after four H2O2 decomposition reactions. A more significant deactivation was observed for the 5% Pd/C and 0,5% Pd/C (both treated with H2). For the 0,5% Pd/C catalyst not exposed to hydrogen, an activation of the catalyst occurred after successive reactions of H2O2 decomposition.